2008
DOI: 10.1038/jp.2008.122
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen lysine administration to neonates with a patent ductus arteriosus: effect on platelet plug formation assessed by in vivo and in vitro measurements

Abstract: Objective: Ibuprofen might have advantages over indomethacin, when used to effectuate closure of a neonate's patent ductus arteriosus (PDA). Several previous studies indicate that platelet plug formation is impaired after administration of indomethacin, but it is not clear whether a similar impairment occurs following ibuprofen dosing.Study Design: We performed template bleeding times and PFA-100 tests (platelet function analyzer) on 20 neonates who had a PDA, before and again at various preset intervals follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…The bleeding times we measured in this study were shorter than those we reported in a recent study of ibuprofen lysine. 1 In fact, the longer bleeding times we observed after three or four doses of ampicillin were similar to the pre-ibuprofen bleeding times we reported earlier. This apparent discrepancy might be because all neonates in our ibuprofen study had already received several doses of ampicillin, and thus they already had some degree of platelet impairment before the ibuprofen doses were begun.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The bleeding times we measured in this study were shorter than those we reported in a recent study of ibuprofen lysine. 1 In fact, the longer bleeding times we observed after three or four doses of ampicillin were similar to the pre-ibuprofen bleeding times we reported earlier. This apparent discrepancy might be because all neonates in our ibuprofen study had already received several doses of ampicillin, and thus they already had some degree of platelet impairment before the ibuprofen doses were begun.…”
Section: Discussionsupporting
confidence: 72%
“…A template bleeding time was performed (by MJS or RDC) using methods described earlier. 1,[10][11][12] The before and after ampicillin bleeding time pairs were always performed by the same technician. Briefly, a bloodpressure cuff appropriate for the infant's size was placed on an upper extremity and set at a pressure equal to the last measured mean blood pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…67 However, ibuprofen does not appear to prolong bleeding times in preterm infants, leading to speculation that it may be preferable to indomethacin for this indication. 68 Although these observations are not definitive, they raise concern that treatment with indomethacin (and possibly with other COX inhibitors) could ultimately increase the number of infants who require ductal ligation, despite inducing early ductal constriction.…”
Section: Prolongation Of Ductal Patencymentioning
confidence: 95%